A direct synthesis of adsorbable hydrochar by hydrothermal conversion of lignin. Issue 9 (2nd May 2016) - Kang, S.; Li, X.; Fan, J.; Chang, J.
ABSTRACT: Hydrothermal conversion of lignosulfonate with or without formaldehyde as polymerization agent was conducted at 320°C. Compared with the hydrochar produced without formaldehyde addition (WF-hydrochar), the yield and surface area of the hydrochar produced with formaldehyde addition (F-hydrochar) increased 33.8 and 46.4%, respectively. The F-hydrochar showed much higher adsorption ability of Cu 2+ than that of WF-hydrochar, while its adsorption ability of methyl orange was a little lower than that of WF-hydrochar. These discoveries explored a high yield of hydrochar production and a potential new application of hydrochar.